Bridges to independence : fostering the independence of new investigators in biomedical research (National Academies Press, 2005)
A rising median age at which PhD s receive their first research grant from the National Institutes of Health (NIH) is among the factors forcing academic biomedical researchers to spend longer periods of time before they can set their own research directions and establish there independence. The fear that promising prospective scientists will choose other career paths has raised concerns about the future of biomedical research in the United States. At the request of NIH, the National Academies conducted a study on ways to address these issues. The report recommends that NIH make fostering independence of biomedical researchers an agency-wide goal, and that it take steps to provide postdocs and early-career investigators with more financial support for their own research, improve postdoc mentoring and establish programs for new investigators and staff scientists among other mechanisms.